(untitled) (Research, Society and Development, 2021)
Among the existing barriers in rural schools, possibly, is the use of technologies as an educational tool. The analyses proposed here is how Information and Communication Technology (ICT) are applied in rural schools, without the necessary use of the internet. Because in the rural environment often does not have the facility to access the internet, the computer science laboratory in schools ends up being forgotten and unused, causing the students to want to study in the urban schools. To better understand this context, the main goal of this study is to recognize the effects of the training of educators and students of a rural school in relation to the possibilities of using information and communication technologies beyond the use of the Internet. The research was conducted at the Escola de Ensino Fundamental São José, a rural school in the municipality of Santa Rosa, in the northwest region of the state of Rio Grande do Sul. It was a qualitative research, through the research-action methodology. The data collection was through a semi-structured interview with the school’s management team, educators, and students. In addition, a training workshop was offered to the students of the seventh, eighth and ninth grades of the school and to the educators for these classes with the purpose of suggesting a way of using technology without the use of the internet, through the technique of stop-motion animation, with the use of resources such as a cell phone or a camera, and a computer.